PENGARUH CAMPURAN LIMBAH AMPAS TEH, AMPAS KOPI DAN KULIT NANAS TERHADAP PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) DENGAN MEDIA HIDROPONIK SEDERHANA SEBAGAI BAHAN AJAR BIOLOGI BERUPA LKPD - Nyimas Chinta Ferdya; Widya Sartika Sulistiani; Muhfahroyin (EDUBIOLOCK, 2024)
This study aimed to (1) Know the effect of a mixture of waste tea grounds, coffee grounds and pineapple peel on the growth of water spinach (Ipomoea reptans Poir) with simple hydroponic media, (2) Know what dose of a mixture of waste tea grounds, coffee grounds and pineapple peel that gives the best effect on the growth of water spinach (Ipomoea reptans Poir) with simple hydroponic media, (3) Know the results of the study can be used as biology teaching material in the form of student worksheet. The type of research used was quantitative using experimental methods and non-probability sampling techniques. This study used a Completely Randomized Design (CRD), applying 4 treatments and 3 replications with P0 (250 ml water), P1 (250 ml POC), P2 (200 ml POC+50 ml water), P3 (150 ml POC+ 100 ml water). Based on the results of the study, it can be concluded that there was an increase in height and number of leaf blades on water spinach (Ipomoea reptans Poir). With the research results, the best plant height was at P3= 20.33 cm and for the best leaf blade results it was at P3= 14 strands. The results of this study can be used as biology teaching material in the form of of student worksheet on growth and development material for SMA class XII. The results of the validation of learning resources by material experts, design experts and linguists concluded that of student worksheet was feasible to use as a learning resource with an average score of 100% material experts, 80% design experts and 90% linguists